1998
DOI: 10.1136/hrt.80.4.349
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peripheral endothelial dysfunction and intimal media thickness in patients with suspected coronary artery disease

Abstract: Conclusions-In patients with clinically suspected coronary artery disease, FAD% discriminates between the presence or absence of coronary artery disease, whereas intimal media thickness is associated more with the extent of coronary artery disease. (Heart 1998;80:349-354)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 30 publications
6
66
1
2
Order By: Relevance
“…In contrast with Enderle and cols. 17 , there was no correlation between the arterial intimal-medial thickening and the degree of coronary obstruction, but the same observations regarding the defi nition of disease severity discussed above must be considered.…”
Section: Chequer Et Al Carotid Intimal-medial Thickening and Endothelmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast with Enderle and cols. 17 , there was no correlation between the arterial intimal-medial thickening and the degree of coronary obstruction, but the same observations regarding the defi nition of disease severity discussed above must be considered.…”
Section: Chequer Et Al Carotid Intimal-medial Thickening and Endothelmentioning
confidence: 88%
“…These data are in accordance with those demonstrated by Enderle and cols. 17 in a group of patients highly suspected of having coronary disease (r=-0.317, p= 0.0004). Campuzano and cols.…”
Section: Chequer Et Al Carotid Intimal-medial Thickening and Endothelmentioning
confidence: 99%
“…Carotid intima-media thickness (CIMT), flow associated dilatation (FAD %) and nitric oxide sensitivity of the smooth muscle cell of the brachial artery to nitroglycerine (GTN %) are legitimate markers of early atherosclerosis (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). CIMT is a surrogate marker for generalized atherosclerosis and imparts prognostic information independent of traditional cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…FAD % is a sensitive predictor of CAD, although it is unable to predict both the extent and the severity of angiographically assessed CAD (12)(13)(14). GTN % is an index of endothelium independent vasodilatation and a reduced GTN % is a valuable marker in predicting more advanced coronary atherosclerosis (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…While QCA and CIMT are associated with prevalent CVD and have strong prognostic value for incident CVD independent of risk profiles [1,3,[6][7][8][9], the diagnostic and prognostic importance of BFMD for CVD is less certain [10]. Although some studies have shown BFMD to be predictive of future coronary events [11,12], only a handful of studies have reported an inverse association between BFMD and CIMT [13][14][15][16][17][18]. The majority of these studies were small, cross-sectional evaluations of men with pre-existing coronary artery disease (CAD) [13,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%